Anti-aging and anti-tumor effect of FPP® supplementation Mariantonia Logozzi, - Mariantonia Logozzi; Rossella Di Raimo; Davide Mizzoni; Stefano Fais (European Journal of Translational Myology, 2020)
The beneficial effect of FPP® as antioxidant is known. Here we summarize recent data supporting future implementation of FPP® in tumor treatment and in controlling aging at the molecular level. We first showed that oral FPP® is able to control tumor growth and with inducing a potent and systemic anti-oxidant reaction (i.e. reduced ROS and increased GSH and SOD-1). Then we showed that FPP® is able to markedly increase the body anti-oxidant reaction together with increasing both telomerase activity in the blood and the telomeres length in bone marrow and ovary of treated mice as compared to the untreated mice.